(untitled) (Al-Qamar, 2021)
Jurisprudence is of special importance in the Islamic sciences because it is on the one hand linked with Quran and Sunnah which are source of Shariah, and on the other hand it is linked with the understanding of the event. In this area of knowledge, Problems are solved in the light of Sharia after understanding Quran and Sunnah. This is a gift from Allah Almighty who bestows on whom He wants. This knowledge is obtained in the form of a divine gift after true commitment to the Shariah. This knowledge gives clarity in confusing ideas. There is a school of thought in Islamic jurisprudence called Fiqh-ul-Hadith. In this school of thought, there is a lot of emphasis on to stick and hold on Hadith and seerah. This knowledge is comprised guidance of various life forms. There are even some skilled persons whose knowledge is benefiting a world. In this article, it is tried to introduce this school of thought of Islamic jurisprudence, its privileges and features, its sources and experts.